Prodromal symptoms in knee osteoarthritis: a nested case–control study using data from the Osteoarthritis Initiative. Issue 7 (July 2015) - Case, R.; Thomas, E.; Clarke, E.; Peat, G.
Summary: Objective: In order to gain a better understanding of the timing of emergent symptoms of osteoarthritis, we sought to investigate the existence, duration and nature of a prodromal symptomatic phase preceding incident radiographic knee osteoarthritis (ROA). Design: Data were from the incidence cohort of the Osteoarthritis Initiative (OAI) public use datasets. Imposing a nested case–control design, ten control knees were selected for each case of incident tibiofemoral ROA between 2004 and 2010 from participants aged 45–79 years. Candidate prodromal symptoms were Western Ontario & McMaster Universities Osteoarthritis Index (WOMAC) and Knee injury and Osteoarthritis Outcome Score (KOOS) subscale scores and individual items, available up to 4 years prior to the time of incident ROA. Multi-level models were used to estimate the length of the prodromal phases. Results: The prodromal phase for subscale scores ranged from 29 months (KOOS Other Symptoms) to 37 months (WOMAC Pain). Pain and difficulty on activities associated with higher dynamic knee loading were associated with longer prodromal phases (e.g., pain on twisting/pivoting (39 months, 95% confidence interval: 13, 64) vs pain on standing (25 months: 7, 42)). Conclusions: Our analysis found that incident ROA is preceded by prodromal symptoms lasting at least 2–3 years. This has potential implications for understanding phasic development and progression of osteoarthritis and for early recognition and management.